Gaya Belajar Siswa Autis di Sekolah Luar Biasa Negeri Pembina Pekanbaru - Yolanda, Windy; Mukhlis, Muhammad (UIR PRESS, 2021)
Autistic students at Pekanbaru Pembina State SLB have their own uniqueness in learning. They have a learning style that is different from other normal children. Especially in SLB Negeri Pembina Pekanbaru. The dominant learning style in autistic children is memorizing the information as it is (rote learner), memorizing the sentence as a whole (gestalt learner), even some who quickly understand the information when given visual learner assistance. Based on this, the authors raised the issue of research regarding Learning Style of Autistic Students in Learning Indonesian Language at Extraordinary Schools (SLB) of Pembina Pekanbaru. This study uses a descriptive method with a quantitative approach. Data were collected using tests from Lakshita's learning style theory (2010). The population in this study were all autistic persons who sat in class VI of the Pembina Negeri Pembina Pekanbaru, amounting to 20 people. The sample used is purposive sampling or purposive sampling. The sample in this study amounted to five autistic children from the VIA and VIB classes. The results of the study found that the learning style of autistic students in Pekanbaru Pembina Negeri Extraordinary Schools tended to use visual learner learning styles. This is based on research findings, the learning style that has the highest value is the visual learning style with an average value of 80% (good). After that followed the Gestalt Learner learning style with an average value of 77% and continued with the learner rote learning style with an average value of 75%. The findings in this study are: First, for the visual learning style of autistic children, it is better to read stories with picture media. They better capture the contents of the reading if helped with pictures. Second, for the Gestalt learner learning style, autistic children tend to memorize sentences in their entirety without understanding the meaning of the word per word contained in the sentence. Third, for the learner rote learning style, autistic children tend to memorize information as it is, without understanding the meaning of the symbols they memorize it. Autistic children prefer lessons that use teaching aids such as pictures, photos, picture books, and posters to attract their learning interest